Criminal Investigation - Stainton, Iain; Ewin, Robert; Blockley, Tony (The Professional Policign Curriculum in Practice, 2022)
Criminal investigation is an essential topic, running through the new national policing curriculum from volume crime to serious organised criminality. This book provides accessible and comprehensive coverage, with case studies and examples to embed understanding, clear links between theory and practice, and a range of critical thinking and review activities. It examines investigation from inception to conclusion, detailing methods, explaining legal requirements and reflecting on past investigations. The contributory roles of specialists and forensic support are examined to provide an inclusive overview of the whole investigative process.The Professional Policing Curriculum in Practice is a new series of books that match the requirements of the new pre-join policing qualifications. The texts reflect modern policing, are up-to-date and relevant, and grounded in practice. They reflect the challenges faced by new students, linking theory to real-life operational practice, while addressing critical thinking and other academic skills needed for degree-level study.